Preventing and Combating Corruption in Nigeria’s Public Procurement: The Pivotal Role of the Bureau of Public Procurement (BPP) - Aigbe, Irene Airen (NIU Journal of Legal Studies, 2026)
Public procurement is one of the most significant avenues through which government provides goods, works, and services to its citizens. It constitutes the primary channel for delivering development and public welfare projects in Nigeria. However, the procurement process has been deeply undermined by entrenched corruption, resulting in waste, inefficiency, and diversion of resources. In an attempt to address these challenges, the National Assembly enacted the Public Procurement Act (PPA) 2007, designed to harmonize procurement practices, promote transparency, and strengthen accountability. The Act further established the Bureau of Public Procurement (BPP) as the regulatory authority mandated to oversee and enforce compliance with its provisions. The PPA incorporates progressive mechanisms aimed at preventing corruption, enhancing competitiveness, and ensuring value for money in public contracting. Yet, despite these frameworks, corruption in public procurement remains pervasive. Institutions such as the Federal Executive Council (FEC), which also functions as a procurement entity, frequently disregard statutory provisions by awarding contracts without due process. Worryingly, members of the FEC who also sit on the National Council on Public Procurement, including the Attorney-General of the Federation and the Minister of Finance, often fail to enforce compliance. Moreover, the National Assembly, vested with constitutional oversight responsibilities, has not consistently exercised its powers to check these infractions. To achieve meaningful reform, the BPP must be empowered and supported to fully discharge its statutory functions. Strengthening its regulatory role is pivotal not only for curbing corruption in procurement but also for advancing Nigeria’s broader anti-corruption agenda. Keywords: Public Procurement, Bureau of Public Procurement, Public Procurement Act 2007, Corruption, Transparency, Accountability, Nigeria, Governance